Diseño de un sistema de evaluación de desempeño por competencias para el personal del área comercial, en la matriz de una empresa de seguros en el periodo junio a noviembre del 2015. - Amaya Murillo, Ruth Alexia (2016)
This paper contains the systematization of the experience gained in the organization, according to the formats stablished by the Salesian Polytechnic University. The topics included in this paper are divided in two categories: first, the systematization's plan and, second, its experience. The purpose of this intervention was to create an achievement evaluation system, this system is based on competences and is addressed to the workers of the commercial area. The research was developed in an Ecuadorian Insurance Company, whose main establishment is located in Quito. This intervention project values the working competences, considering the company's competences dictionary, which was used to guide its human resources. This dictionary includes eleven competences that were exclusively developed for the organization. Among these, five were chosen to create a behavior dictionary, and the achievement evaluation formulary for the commercial area. The chosen competences were: Communication (CO), Leadership and Influence (LI), Customer Orientation (OC), Results Orientation (OR), Teamwork (TE). This model will allow to evaluate the collaborators' achievement and properly orientate their development plans, through objective information, in order to focalize investments in a proper way. Besides, it will allow them to be more rigorous and objective in the decisions made within the organization.